Influence Of Internal Factors And External Factors on Going Concern Audit Opinion - Sohibunajar, Sohibunajar; Jazuli, Akmal Lutfi; Ersyafdi, Ilham Ramadhan (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2021)
Abstract The purpose of this research was to test effect of internal factors among others are disclosure, debt default, company’s financial condition, liquidity, cash flow, company growth, and external factor among others are opinion Shopping, audit client tenure, previous year’s audit opinion, audit lag on going concern audit opinion. The population in this research are all companies listed in the SRI-KEHATI Indeks periods 2009-2019. There were 11 companies were selected as sample base on purposive sampling method. To analyze the data using logistic regression analysis. The result of this research show that audit client tenure have effect on going concern audit opinion. While disclosure, debt default, company’s financial condition, liquidity, cash flow, company growth, opinion shopping, previous year’s, and audit lag have no effect on going concern audit opinion. Keywords: Internal Factor, External Factor, and Going Concern Audit Opinion